Treatment of Mycobacterium avium Complex Lung Disease With Clofazimine. Issue 5 (September 2016) - Harrington, John S.; Zappetti, Dana
Abstract : Synopsis : Mycobacterium avium and Mycobacterium intracellulare, collectively known as the M. avium complex, are the most common causes of nontuberculous mycobaterial lung disease. Treatment of M. avium complex lung disease is challenging, as it requires patients to adhere to a multidrug regimen that is notorious for adverse drug effects. In this retrospective study by Jarand et al, clofazimine-containing regimens exhibited higher sputum conversion rates than rifampin-containing regimens. Rates of microbiologic relapse and retreatment were similar between the 2 groups. Source : Jarand J, Davis JP, Cowie RL, et al. Long-term follow-up of Mycobacterium avium complex lung disease in patients treated with regimens including clofazimine and/or rifampin." Chest. 2016; 149(5): 1285–293.